2022
DOI: 10.1088/1674-1137/ac6dc8
|View full text |Cite
|
Sign up to set email alerts
|

Shadow thermodynamics of an AdS black hole in regular spacetime *

Abstract: The dependence of the black hole (BH) shadow and thermodynamics may be structured in the regular spacetime. Taking the regular Bardeen-AdS BH as an example, the relationship between the shadow radius and the event horizon radius is derived. It is found that these two radii display a positive correlation, implying that the BH temperature can be rewritten as a function of shadow radius in the regular spacetime. By analyzing the phase transition curves under the shadow context, we found that the shadow radius can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…It can be found that when the shadow radius is smaller than a certain value, the temperature increases from the center to the boundary of the shadow. Then, the temperature oscillates as the shadow radius increases, i.e., the N-type change trend [68]. Figs.…”
Section: Thermal Profile Of the Hayward-ads Bhmentioning
confidence: 95%
See 1 more Smart Citation
“…It can be found that when the shadow radius is smaller than a certain value, the temperature increases from the center to the boundary of the shadow. Then, the temperature oscillates as the shadow radius increases, i.e., the N-type change trend [68]. Figs.…”
Section: Thermal Profile Of the Hayward-ads Bhmentioning
confidence: 95%
“…[65]. Fairly recently, the microstructure states and thermal profiles of different kinds of AdS BHs were studied using shadow formalism [66][67][68][69]. Given the significance of BH thermodynamics and inspired by these pioneering works, we study the thermodynamics of the Hayward-AdS BH with the shadow.…”
Section: Introductionmentioning
confidence: 99%
“…Besides Q e and Φ H , the other macroscopic parameters of the Hayward class BHs are given as follows, (ii) Bardeen-AdS class BHs [10,40]. One can introduce a negative cosmological constant Λ into the action for the Bardeen class BHs, yielding…”
Section: Jcap03(2024)053mentioning
confidence: 99%
“…In particular, it has been shown that the black hole shadows could provide correct information concerning the small/large black hole phase structure and the involved microstructure [41]. It has been shown that the relation between the shadows and the thermodynamics of the black hole has been also developed for regular space-times [42]. Using the elliptic function analysis, it has been explored further a fundamental connection between the AdS black hole thermodynamics and the deflection angle of the light rays.…”
Section: Jcap11(2023)094mentioning
confidence: 99%